Walnut oil-alpha-linolenic acid type structure lipid microcapsule and preparation method thereof

By preparing walnut oil-α-linolenic acid-type structural lipid microcapsules, the problem of structural lipids being prone to oxidation and deterioration is solved, and its good thermal stability and anti-oxidation protection ability is achieved, which extends storage time and improves bioavailability.

CN119605878APending Publication Date: 2025-03-14SHIHEZI UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411836113.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Structural lipids are prone to oxidation and deterioration and should not be stored for a long time, which affects the storage and edible safety of their applications in food, medicines, cosmetics and other fields.

Method used

The preparation method of walnut oil-α-linolenic acid-type structural lipid microcapsules is adopted. By stirring walnut oil-α-linolenic acid with soy protein isolate, β-cyclodextrin and other materials in a shear emulsifier, and forming microcapsules through freeze-drying, effectively preventing the oxidation and deterioration of the oil and fat.

Benefits of technology

The good thermal stability and antioxidant protection of structural lipids are achieved, which extends their storage time, and improves bioavailability through sustained release characteristics to meet specific health needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119605878A_ABST
    Figure CN119605878A_ABST
Patent Text Reader

Abstract

The invention discloses a walnut oil-alpha-linolenic acid type structure lipid microcapsule and a preparation method thereof, and relates to the technical field of biology, the walnut oil-alpha-linolenic acid type structure lipid microcapsule comprises a wall material, a core material and a compound emulsifier, the wall material is a compound wall material solution, the compound wall material solution comprises soybean protein isolate, beta-cyclodextrin and distilled water, and the core material is a compound emulsifier. The addition ratio of the soybean protein isolate to the beta-cyclodextrin is 1: 3; the core material is walnut oil-alpha-linolenic acid structure grease; the compound emulsifier comprises monoglyceride and sucrose ester, the wall material, the core material and the compound emulsifier are uniformly stirred under the action of a shearing emulsifying machine to form an oil-in-water emulsion, the oil-in-water emulsion is freeze-dried to form the microcapsule, and the preparation method comprises the following steps: preparing the structural grease, preparing the wall material, homogenizing, emulsifying and freeze-drying. The invention provides the preparation method of the structural lipid microcapsule which is relatively high in embedding rate, relatively high in antioxidant protection capability on grease and relatively good in slow release characteristic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biotechnology, and specifically relates to a walnut oil-alpha-linolenic acid type structured lipid microcapsule and a preparation method thereof. Background Art

[0002] Structured lipids are a new type of functional lipids with broad application prospects and research value. In the food industry: structured lipids can be used as a substitute for low-fat foods, with the effects of regulating blood lipids, lowering cholesterol, and preventing cardiovascular diseases. In addition, structured lipids can also be used as functional additives to improve the texture and taste of food. In the pharmaceutical industry: structured lipids have good biocompatibility and biodegradability, and can be used as drug carriers or controlled-release agents to improve the bioavailability of drugs and reduce toxic side effects. In the cosmetics industry: structured lipids have good antioxidant and moisturizing properties, and can be used in skin care products, lipsticks, and lip balms; in the fuel industry: structured lipids can be used as raw materials for biodiesel, which has the advantages of environmental protection and renewability compared to traditional petroleum fuels.

[0003] Functional plant oils (walnut oil, olive oil, etc.) are rich in unsaturated fatty acids and have certain potential in controlling blood lipids and preventing cardiovascular diseases. In recent years, with the enhancement of people's health awareness and the adjustment of dietary structure, the market demand for functional plant oils has gradually increased. However, functional plant oils are prone to oxidation and deterioration, which affects the storage and consumption safety of themselves and their functional foods. Microencapsulation technology can effectively prevent the oxidation and deterioration of functional plant oils by encapsulating oils.

[0004] Therefore, in order to solve the above technical problems, a new technical solution needs to be provided to solve this technical problem, especially a walnut oil-α-linolenic acid type structured lipid microcapsule and a preparation method thereof. Summary of the invention

[0005] The purpose of the present invention is to solve the problems that the structured lipids in the existing method are easy to oxidize and deteriorate and are not suitable for long-term storage, and provide a walnut oil-α-linolenic acid type structured lipid microcapsule and a preparation method thereof.

[0006] In order to achieve the above-mentioned purpose, the present invention provides the following technical scheme: a walnut oil-α-linolenic acid type structural lipid microcapsule, comprising a wall material, a core material and a compound emulsifier, wherein the wall material is a compound wall material solution, the compound wall material solution comprises soy protein isolate, β-cyclodextrin and distilled water, and the addition ratio of the soy protein isolate and the β-cyclodextrin is 1:3; the core material is walnut oil-α-linolenic acid structural lipid; the compound emulsifier comprises monoglyceride and sucrose ester, and the wall material, the core material and the compound emulsifier are stirred evenly under the action of a shear emulsifier to form an oil-in-water emulsion and freeze-dried to form microcapsules.

[0007] Preferably, the addition ratio of the core material, the wall material and the compound emulsifier is 1:4:0.4-0.5, and the walnut oil-α-linolenic acid structural lipid is a structural lipid rich in α-linolenic acid at the sn-2 position.

[0008] The present invention also provides a method for preparing walnut oil-α-linolenic acid type structured lipid microcapsules, comprising the following steps:

[0009] Step 1: Preparation of structural lipids rich in α-linolenic acid at the sn-2 position;

[0010] S1. Enzymatic acid hydrolysis

[0011] S11. Mix the α-linolenic acid product and walnut oil in a ratio of 1:1-5:1 (mol / mol) and deionized water in a ratio of 1%, and place in a screw-stoppered test tube;

[0012] S12. 1-20% (w / w) lipase Novozym 435 was added to the test tube;

[0013] S13. The reactants are thoroughly mixed, the test tube is filled with nitrogen to exclude oxygen, and then the test tube is tightly sealed;

[0014] S14. Place the test tube on a shaker, set the speed to 200 r / min, and react at a temperature of 35-75°C for 8-48 hours to obtain an acid hydrolysis product;

[0015] S2. Molecular distillation purification

[0016] S21. placing the product of the enzymatic acid hydrolysis in a molecular distillation apparatus, setting the parameter conditions of the molecular distillation apparatus; performing molecular distillation on the enzymatic acid hydrolysis product to purify the crude product of the acid hydrolysis product;

[0017] Step 2: Weigh 10-18g / 100mL of the composite wall material, dissolve it in 100mL of distilled water, and stir it at a constant temperature of 60°C for 30min using a magnetic water bath stirring pot to dissolve evenly; the composite wall material is prepared by using soy protein isolate and β-cyclodextrin in a ratio of 1:3 (w / w);

[0018] Step 3: Add 2.0-6.0 g of the structured lipid product obtained in step 1, add 0.2-0.6 g / 100 mL of a compound emulsifier, and stir evenly under the action of a high-speed shear emulsifier to form a primary emulsion (15000 r / min 5 min); the compound emulsifier is prepared by using a monoglyceride: sucrose ester ratio of 1:1 (w / w);

[0019] Step 4: homogenize, freeze-dry and store the obtained microcapsule product in a sealed container away from light.

[0020] Preferably, the parameter conditions of the molecular distillation apparatus in step 1 are: preheating 80°C, feed 2mL / min, wall temperature 180°C, scraper 100r / min, condensed water 25°C, and pressure 1Pa.

[0021] Preferably, in step 1, the molar ratio of α-linolenic acid to walnut oil is 3:1, the amount of lipase is 10%, the reaction temperature is 55° C., and the reaction time is 24 h.

[0022] Preferably, in step 1, the molar ratio of α-linolenic acid to walnut oil is 2.65:1, the amount of lipase is 7.65%, the reaction temperature is 55° C., and the reaction time is 38 h.

[0023] Preferably, the α-linolenic acid content in the α-linolenic acid product in step 1 is ≥ 70%.

[0024] Preferably, the amount of wall material added is 10 g / 100 mL, that is, 2.5 g / 100 mL of structural fat is added, and the amount of emulsifier added is 0.6 g / 100 mL.

[0025] The beneficial effects of the present invention are:

[0026] Thermogravimetric analysis of the product prepared by the present invention revealed that the microcapsules had good thermal stability, and only when the temperature exceeded 182°C did a significant mass change occur, showing its superior heat resistance. FTIR analysis strongly proved that the structural lipids were effectively and tightly wrapped by soy protein isolate (SPI) and β-cyclodextrin (β-CD), ensuring the stability of the core material. Further storage stability tests showed that after 60 days of storage under different temperature conditions (4°C, 25°C, 40°C, 60°C), the peroxide value of the microcapsules was significantly reduced compared with the unencapsulated structural lipids, which were reduced by 1.02 times, 1.06 times, 1.01 times and 1.11 times, respectively, highlighting its excellent antioxidant protection ability. In vitro simulated digestion experiments revealed the unique sustained-release characteristics of the microcapsules, that is, most of the core material was gradually released in the intestinal stage. This design not only improves bioavailability, but also helps to control the release rate of nutrients to meet specific health needs. Compared with spray drying, freeze drying can produce higher quality powders than spray drying. At the same time, functional walnut oil structured lipid microcapsules are prepared by using composite wall materials combined with freeze drying to solve the problems of oil flavor deterioration and easy oxidation.

[0027] In terms of preparation method, the present invention uses an enzymatic acid hydrolysis method to prepare walnut oil-α-linolenic acid structured lipids, and the total access rate and sn-2 position access rate of α-linolenic acid can reach 20.46% and 10.33%, respectively. The product access rate is high, and the yield is more than 70%, and the yield of the structured lipid product is high. After molecular distillation purification, the acid value of the product is reduced from 88.7mg KOH / g to 0.43mgKOH / g, and the triglyceride (TAG) content in the product reaches more than 90%, which is easy to purify and has a high purity. 75.35% of the triglyceride products prepared contain α-linolenic acid. At the same time, the lipase can be reused more than 10 times and still maintain a high activity, reducing the production cost. Under optimal conditions, the prepared microcapsule sample exhibits an excellent embedding efficiency of 98.00%±0.46%. The observation results of scanning electron microscopy and laser confocal microscopy showed that walnut oil-α-linolenic acid structured lipid microcapsules (ALA-SLM) presented an approximately spherical structure, with a particle size distribution concentrated between 1-10 μm, and its good uniformity was further verified by the Span value of 1.92. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The enzymatic acid hydrolysis conditions of the present invention are screened Figure 1 .

[0029] Figure 2 The enzymatic acid hydrolysis conditions screening of the present invention Figure 2 .

[0030] Figure 3 The enzymatic acid hydrolysis conditions screening of the present invention Figure 3 .

[0031] Figure 4 The enzymatic acid hydrolysis conditions screening of the present invention Figure 4 .

[0032] Figure 5 It is a response surface diagram of the total access rate of ALA affected by the interaction of factors in the present invention.

[0033] Figure 6 It is a response surface diagram of the interaction of factors affecting the sn-2 access rate of ALA in the present invention.

[0034] Figure 7 This is a diagram of the lipase reuse experiment of the present invention.

[0035] Figure 8 It is a screening diagram of the microcapsule process conditions of the present invention.

[0036] Fig. 9 Schematic diagram of the microcapsule sample of the present invention.

[0037] Fig.10is a scanning electron microscope image of the microcapsule of the present invention.

[0038] Fig.11 This is a laser confocal image of the microcapsule of the present invention.

[0039] Fig.12 It is a diagram of the particle size distribution range and related parameters of the microcapsules of the present invention.

[0040] Fig.13 It is the Fourier infrared spectrum of the microcapsule of the present invention.

[0041] Fig.14 It is the thermogravimetric curve of the microcapsule of the present invention.

[0042] Fig.15 Graph showing the effect of temperature on the peroxide value during storage of (left) ALA-SLM and (right) ALA-SL.

[0043] Fig.16 It is the release rate curve of the microcapsule of the present invention in an in vitro simulated digestion environment. DETAILED DESCRIPTION

[0044] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.

[0045] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0046] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0047] Professional term explanation: Triglycerides have three fatty acid binding sites (sn-1, sn-2 and sn-3), among which the fatty acid at sn-2 is easier for the human body to absorb. The sn-2 in this specification refers to the second fatty acid binding site of triglycerides. Walnut oil (WO), alpha-linolenic acid (ALA), walnut oil-alpha-linolenic acid structured lipid (ALA-SL), walnut oil-alpha-linolenic acid structured lipid microcapsules (ALA-SLM).

[0048] The Chinese meaning of the English abbreviations: L (lauric acid), MA (myristic acid), PA (palmitic acid), SA (stearic acid), OA (oleic acid), LA (linoleic acid), ALA (α-linolenic acid).

[0049] 1. Embodiment:

[0050] (I) Preparation of structural lipids

[0051] Enzymatic acid hydrolysis: Mix α-linolenic acid product (purity ≥ 70%), walnut oil in a ratio of 1:1-5:1 (mol / mol) and deionized water at a ratio of 1%, and place in a spiral stopper test tube. Subsequently, add 1-20% (w / w) of lipase Novozym 435 to the test tube. After ensuring that all reactants are fully mixed, the test tube is filled with nitrogen to exclude oxygen, and then the test tube is tightly sealed. Next, the test tube is placed on a shaker, the speed is set to 200r / min, and the acid hydrolysis product can be obtained after 8-48h of reaction at a temperature of 35-75°C. This process aims to produce the target product by acidolysis of walnut oil and α-linolenic acid (ALA) through enzyme catalysis.

[0052] Taking into account the acid value and yield of the product, the product of enzymatic acid hydrolysis was placed in a molecular distillation apparatus, and the parameter conditions of the molecular distillation apparatus were set: preheating 80°C, feed 2mL / min, wall temperature 180°C, scraper 100r / min, condensed water 25°C, pressure 1Pa, and molecular distillation was performed to purify the crude product rich in α-linolenic acid structural lipids (ALA-SL) at the sn-2 position, and a secondary heavy phase was obtained through secondary molecular distillation.

[0053] In some embodiments, in step (1), the molar ratio of α-linolenic acid to walnut oil is 3:1, the dosage of Novozym435 lipase is 10%, the reaction temperature is 55° C., and the reaction time is 24 h.

[0054] In a more preferred embodiment, in step (1), the molar ratio of α-linolenic acid to walnut oil is 2.65:1, the dosage of Novozym435 lipase is 7.65%, the reaction temperature is 55° C., and the reaction time is 38 h.

[0055] The comparative experiment of optimizing experimental parameter conditions is as follows:

[0056] (II) Preliminary screening of conditions for enzymatic acid hydrolysis reaction

[0057] (1) Substrate molar ratio

[0058] The enzymatic reaction was carried out at five gradient molar ratios of α-linolenic acid (ALA) / walnut oil (mol / mol) substrate, namely 1:1, 2:1, 3:1, 4:1, and 5:1. The other reaction conditions were: 1% water content in the system, 10% enzyme loading, 55°C reaction temperature, and 24h reaction time.

[0059] like Figure 1 As shown, when the ratio of α-linolenic acid (ALA) / walnut oil is 3:1, the total accession rate and sn-2 accession rate of α-linolenic acid (ALA) reach 14.87% and 5.57% respectively. When the substrate ratio exceeds 3:1, the increase in the content of α-linolenic acid (ALA) in walnut oil is not obvious, that is, the substrate molar ratio is determined to be 2:1, 3:1, and 4:1 for optimization experiments.

[0060] (2) Enzyme loading

[0061] The enzymatic reaction was carried out at five gradient enzyme loadings (w / w) of 1, 5, 10, 15, and 20%, respectively. Other reaction conditions were: system water content of 1%, substrate molar ratio of 3:1, reaction temperature of 55°C, and reaction time of 24h.

[0062] like Figure 2 As shown in the figure, when Novozym 435 is used, the total access rate of α-linolenic acid (ALA) increases with the increase of enzyme dosage, but when the enzyme dosage is greater than 10%, the total access rate of α-linolenic acid (ALA) decreases. Since the water content of the system does not increase with the increase of enzyme dosage, the water content in the system is insufficient for the enzyme to exert its maximum activity, thereby reducing the access rate. That is, the enzyme loading of 5%, 10%, and 15% was determined for optimization experiments.

[0063] (3) Reaction temperature

[0064] The enzymatic reaction was carried out at five gradient temperatures of 35°C, 45°C, 55°C, 65°C and 75°C, respectively. Other reaction conditions were: system water content 1%, substrate molar ratio 3:1, enzyme loading 10% and reaction time 24h.

[0065] like Figure 3 As shown in the figure, when the temperature rises from 35°C to 55°C, the total accession rate and sn-2 accession rate of α-linolenic acid (ALA) gradually increase, and the accession rates are 13.8% and 2.31%, respectively. When the temperature reaches 55°C, the accession degree of α-linolenic acid (ALA) is the largest. However, when the temperature continues to rise, the accession degree decreases slightly, which may be due to the inactivation of some enzymes, reducing the catalytic efficiency. It can be seen that the optimal temperature for Novozym 435 to catalyze this acidolysis reaction is 45-65°C. That is, the reaction temperatures of 45°C, 55°C, and 65°C were determined for optimization experiments.

[0066] (4) Response time

[0067] The enzymatic reaction was carried out at five gradient temperatures of 8, 10, 12, 24, 36 and 48 h, respectively. Other reaction conditions were: 1% water content in the system, 3:1 substrate molar ratio, 10% enzyme loading and 55°C reaction temperature.

[0068] like Figure 4 As shown, in the first 8 to 36 hours, the total accession rate of α-linolenic acid (ALA) increased from 7.59% to 16.42%, and the accession rate at the sn-2 position increased from 0.92% to 5.72%. After 36 hours, the accession rate of α-linolenic acid (ALA) did not increase significantly, indicating that the best time for Novozym 435 to catalyze this acidolysis reaction is 24 to 48 hours. That is, the reaction time of 24 hours, 36 hours, and 48 hours was determined for optimization experiments.

[0069] (III) Experimental condition parameters of enzymatic acid hydrolysis process response surface optimization

[0070] The influencing parameters of the response surface optimization experiment were selected from the results of the initial screening of conditions for the enzymatic acid hydrolysis reaction. Using the above results, the following experiments were carried out.

[0071] The substrate molar ratio (A), enzyme loading (B), reaction temperature (C) and reaction time (D) were selected as influencing factors, and the total accession rate of α-linolenic acid (ALA) and the sn-2 accession rate of α-linolenic acid (ALA) were used as response values. The response surface optimization experiment with four factors and three levels was designed using DesignExpert 8.0. In order to analyze and optimize the influence of process parameters on the response variables, the RSM design included 29 groups of randomized experiments. The experiment was carried out randomly, and the experimental values ​​were averaged. The total accession rate and sn-2 accession rate were measured by GB5009.168-2016 National Food Safety Standard for the Determination of Fatty Acid Content in Food and GB / T24894-2010 for the Determination of 2-position of Triglycerides in Animal and Plant Oils and Fats, respectively. The response surface optimization design scheme and results are shown in Table 1.

[0072] Table 1 Response surface optimization design scheme and results

[0073]

[0074]

[0075] With A, B, C, and D as independent variables and Y1 and Y2 as response values, the optimized fitting quadratic equations of the total access rate of ALA and the sn-2 access rate of ALA were obtained through analysis with Design Expert 8.0.6 software:

[0076] Y1(%)=20.40+2.36A+2.59B+0.9308C+0.4475D+0.5150AB+0.1000AC-0.2700AD+0.7275BC-0.0075BD-0.8450CD-2.10A2-3.37B2-2.08C2-1.10D2

[0077] Y2(%)=10.59+0.9867A+1.19B+0.4117C+0.3467D+0.3475AB+0.4825AC-0.0 650AD-0.0950BC+0.2875BD+0.0275CD-0.5077A2-1.31B2-1.42C2-0.6952D2

[0078] Table 2 Regression analysis

[0079]

[0080] Note: P<0.05 indicates statistical significance; P<0.01 indicates relatively significant statistics; P<0.001 indicates extremely significant statistics

[0081] In line with the expected results, all the first-order coefficients are positive, which means that each factor has a positive direct impact on the results; while the second-order coefficients are all negative, indicating that the impact of each factor on the results has a nonlinear decreasing effect. At the same time, the cross-term coefficients vary in positive and negative, revealing that when the factors work together, they may produce both synergistic and offsetting effects, that is, there are complex interactions between the factors. Figure 5 and Figure 6 As shown in the figure, the 3D surface plot generated by the response surface model can well explain the relationship between reaction parameters and response values. The maximum total ALA accession rate and sn-2 position accession rate appear in the range of higher substrate ratio (2.00-3.00) and higher reaction temperature (50.0-60.0℃).

[0082] Figure 5 (a) substrate molar ratio and enzyme loading, (b) substrate molar ratio and reaction temperature, (c) substrate molar ratio and reaction time, (d) enzyme loading and reaction temperature, (e) enzyme loading and reaction time, (f) reaction temperature and reaction time. Figure 6 (a) substrate molar ratio and enzyme loading, (b) substrate molar ratio and reaction temperature, (c) substrate molar ratio and reaction time, (d) enzyme loading and reaction temperature, (e) enzyme loading and reaction time, (f) reaction temperature and reaction time.

[0083] based on Figure 5 and Figure 6Based on the 3D surface data analysis, we derived a set of finely optimized production process parameters, including: the substrate molar ratio was set to a precise ratio of 2.65:1, the enzyme addition was fine-tuned to 7.65% to maximize efficiency, the reaction temperature was controlled at 55°C to maintain optimal enzyme activity, and the reaction time was optimized to 38h to ensure complete reaction. Under this optimized parameter framework, we used a predictive model to estimate the overall accession rate of ALA and its accession rate specific to the sn-2 position, which reached the expected 20.58% and 10.47%, respectively.

[0084] (IV) Figure 5 and Figure 6 Verification of optimized parameters obtained in experiments

[0085] In order to verify the effectiveness of the optimization strategy and the accuracy of the prediction model, we designed and executed a set of experiments in strict accordance with the above steps and the above optimization conditions. The experimental results show that the measured value of the overall access rate of α-linolenic acid (ALA) is 20.46%, while the specific access rate of α-linolenic acid (ALA) at the sn-2 position is 10.33%. These two data are highly consistent with the model prediction value, with very small deviations, which strongly proves the accuracy and reliability of the established response surface methodology (RSM) model. This verification process not only confirms the scientific nature of the optimization conditions, but also provides a solid theoretical basis and data support for subsequent process amplification and production applications. It can be seen that the experimental results are very consistent with the predicted results.

[0086] Through the above, preliminary screening is carried out through experiments, and the best experimental parameter data is obtained after optimization calculation through response surface. After verification, it is basically consistent with the actual conclusion, so that an experimental method with high output rate is obtained through optimized experimental condition ratio.

[0087] 2. Experimental analysis of lipase reuse of structural lipids of the present invention

[0088] like Figure 7 As shown, after the immobilized lipase Novozym 435 in the reaction system was treated (washed and filtered 2-3 times with petroleum ether and dried at a constant temperature in a fume hood), it was recovered and directly applied to subsequent multiple test batches, and the stability and reusability of its catalytic activity were deeply evaluated. Figure 7As shown, in the continuous multiple rounds of reactions using the optimized process conditions of the present invention, the immobilized enzyme Novozym 435 still has durability and catalytic efficiency. Specifically, the immobilized enzyme can be reused at least more than ten times without significant performance degradation. Even in the eighth reaction, the total access rate of α-linolenic acid (ALA) is still as high as 17.80%. Compared with the initial reaction efficiency, this value shows that its catalytic activity can still be maintained at a high level of about 80%. The lipase used in the method of the present invention can be recycled and reused multiple times, thereby further reducing the cost of the present invention.

[0089] 3. Analysis of distillation purity and product yield of structural lipids

[0090] As can be seen from Table 3, before distillation, the sample had a high content of free fatty acids (FFA) and also contained a small amount of monoacylglycerol (MAG) and diacylglycerol (DAG). However, after distillation, a significant decrease in the content of FFA was observed, while the content of MAG and DAG also decreased. It is worth noting that the content of triglycerides (TAG) increased significantly, and its relative content reached 93.4%. This change indicates that the distillation process effectively purified TAG and reduced the content of other impurities, thereby improving the quality of the sample.

[0091] Table 3 Comparison of purity before and after molecular distillation

[0092] MAG (%) DAG(%) TAG(%) FFA(%) Before molecular distillation <![CDATA[5.60±1.71 a ]]> <![CDATA[1.95±0.13 a ]]> <![CDATA[45.6±1.71 b ]]> <![CDATA[46.8±1.81 a ]]> After molecular distillation <![CDATA[3.40±0.95 a ]]> <![CDATA[1.82±0.15 a ]]> <![CDATA[93.4±0.95 a ]]> <![CDATA[1.38±0.03 b ]]>

[0093] The sn-2 position-rich α-linolenic acid structural lipids (ALA-SL) were purified by molecular distillation, and the type composition of the products was analyzed by ultra-performance liquid chromatography-quadrupole tandem time-of-flight mass spectrometry (UPLC-Q-TOF-MS).

[0094] Table 4 TAG type composition of ALA-SL products after molecular distillation

[0095]

[0096]

[0097] The specific triglyceride (TAG) structure type results are shown in Table 4. A total of 33 types of triglycerides (TAG) were identified, of which 75.35% contained α-linolenic acid (ALA). In this study, OA-ALA-ALA was the most abundant, accounting for 12.26%. Therefore, the content of triglycerides (TAG) rich in α-linolenic acid (ALA) in the product of the present invention is high, and the product prepared by this experimental method has a high yield.

[0098] The above is the preparation method of the structured lipid of the present invention. The method uses an enzymatic acid hydrolysis method to prepare the sn-2 position-rich α-linolenic acid structured lipid, and the total access rate of α-linolenic acid and the sn-2 position access rate can reach 20.46% and 10.33%. After molecular distillation purification, the acid value of the product is reduced from 88.7 mg KOH / g to 0.43 mg KOH / g. The yield of the structured lipid product is 41.3% and the yield is 81.6%. At the same time, the lipase can be reused more than 10 times and still maintain a high activity.

[0099] 4. Preparation of the microcapsule product of the present invention

[0100] (I) Preparation

[0101] Weigh 10g of the composite wall material (soy protein isolate: β-cyclodextrin = 1:3 (w / w)) and dissolve it in 100mL of distilled water. Use a magnetic water bath stirring pot to stir at 60°C for 30min to dissolve evenly. Add 2.5g of walnut oil and 0.6g of the composite emulsifier (monoglyceride: sucrose ester = 1:1 (w / w)). Stir evenly under the action of a high-speed shear emulsifier to form a primary emulsion (15000r / min 5min). Homogenize and freeze-dry the obtained microcapsule product and seal it to protect it from light.

[0102] In a more preferred embodiment, the core-to-wall ratio in step (1) is 1:4, and preferably, the addition ratio of the core material, wall material and compound emulsifier is 1:4:0.4-0.5; that is, the added amount of wall material is 10g / 100mL, 2.5g / 100mL structural lipid, and the added amount of emulsifier is 0.6g / 100mL.

[0103] (II) Preliminary screening of process conditions for microcapsule products

[0104] Combined with the preliminary experimental results, the compound wall material ratio was determined to be 3:1 (w / w)), the compound emulsifier ratio was 1:1 (w / w), and the embedding rate was used as an indicator to conduct single factor tests on the core-to-wall ratio, wall material addition amount, and emulsifier addition amount. The experimental results are as follows Figure 8 shown.

[0105] (1) Core-to-wall ratio

[0106] A total of 14 g / 100 mL of wall material was added and the compound emulsifier was added in an amount of 0.4 g / 100 mL. The effects of core-to-wall ratios of 1:5, 1:4.5, 1:4, 1:3.5, and 1:3 (w / w) on the microcapsule embedding efficiency were studied.

[0107] (2)Amount of wall material added

[0108] Under the conditions of core-to-wall ratio of 1:4 (w / w) and compound emulsifier addition of 0.4 g / 100 mL, the effect of wall material addition of 10, 12, 14, 16, and 18 g / 100 mL on the microcapsule embedding efficiency was studied.

[0109] (3) Emulsifier addition amount

[0110] Under the conditions of adding 14g / 100mL wall material (soy protein isolate: β-cyclodextrin) and a core-wall ratio of 1:4 (w / w), the effect of emulsifier addition amounts of 0.2, 0.3, 0.4, 0.5, and 0.6g / 100mL on the microcapsule embedding efficiency was studied.

[0111] With the increase of core-to-wall ratio, the amount of composite wall material added, and the amount of composite emulsifier added, the microcapsule embedding rate showed a trend of first rising, reaching a peak, and then decreasing. The conditions with the highest embedding rate were: core-to-wall ratio 1:4 (98.41±0.82%); wall material addition 12g / 100mL (81.65±0.74%); emulsifier addition 0.5g (84.23±0.83%). From the results of the single factor experiment, it can be seen that the core-to-wall ratio levels of 1:4.5, 1:4 and 1:3.5, the wall material addition amount of 10g / 100mL, 12g / 100mL and 14g / 100mL, the wall-to-core ratio of 1.5:1, 2:1 and 2.5:1, and the emulsifier addition amount of 0.4g / 100mL, 0.5g / 100mL and 0.6g / 100mL were selected as subsequent orthogonal optimization.

[0112] (III) Orthogonal optimization experiment of microcapsule product process conditions

[0113] According to the results of the above single factor experiment, A: core-to-wall ratio, B: wall material addition amount and C: emulsifier addition amount were selected for three-factor three-level orthogonal experiment.

[0114] Table 5 Orthogonal test L9(3 4 ) Factors and levels

[0115] level A B C 1 1∶4.5 10 0.4 2 1∶4 12 0.5 3 1∶3.5 14 0.6

[0116] As shown in Table 6, the influence of each factor on the microcapsule embedding rate is A>B>C, that is, core-to-wall ratio> wall material addition> emulsifier addition. The optimal combination obtained from the orthogonal optimization table is A2B1C3, that is, core-to-wall ratio 1:4, wall material addition amount is 10g / 100mL, and emulsifier addition amount is 0.6g / 100mL. Walnut oil-α-linolenic acid structured lipid microcapsules (ALA-SLM) samples under the optimal process conditions are as follows Fig. 9 As shown, the powder is light white.

[0117] Table 6 Orthogonal test results

[0118]

[0119]

[0120] V. Analysis of the physical and chemical properties of the microcapsule product of the present invention

[0121] (I) Determination of basic physical and chemical indicators

[0122] (1) Embedding rate

[0123] Weigh 1.00g of microcapsule product into a 50mL conical flask, add 20mL of n-hexane and ultrasonically crush for 20min, filter, transfer the filtrate to a constant weight round-bottom flask, evaporate the solvent at 50℃, dry in a 50℃ drying oven to constant weight, calculate the mass difference before and after the round-bottom flask, that is, the total oil content of the microcapsule. To determine the surface oil content of the microcapsule, weigh 1.00g of the product into a 50mL conical flask, add 20mL of n-hexane and gently vibrate and extract for 30 seconds. After filtration, evaporate the filtrate and dry it to constant weight. By comparing the mass difference before and after the round-bottom flask, the oil content can be accurately calculated.

[0124]

[0125] (2) Moisture content

[0126] Weigh 1.000 g of granules, place in a weighing bottle, and bake in an oven at 105°C for 3 to 4 h. Take out and place in a desiccator, cool for 0.5 h, weigh until constant weight is reached, and calculate the moisture content.

[0127] (3) Density

[0128] Pour the microcapsules into a 10mL measuring cylinder and fill them to the scale line. Record the mass of the filled microcapsules (m) and the filling volume of the measuring cylinder (10mL). Calculate the bulk density of the microcapsules according to the following formula. Then tap the measuring cylinder lightly on the sponge pad so that there is no obvious change in the sample volume. Record the volume of the sample at this time as V, and then calculate the tap density of the microcapsules.

[0129]

[0130] (4) Angle of repose θ

[0131] Weigh 10 g of microcapsules into a funnel and let the microcapsules fall and accumulate on a round glass plate. Measure the microcapsule pile height (H) and pile coverage radius (R), and calculate the microcapsule repose angle (θ) according to the following formula.

[0132]

[0133] (5) Solubility:

[0134] The solubility of the microcapsules was calculated by measuring the solid content in the solution.

[0135] As shown in Table 7, the embedding rate of the microcapsule product is 98.00±0.46%, indicating that the embedding effect of walnut oil-α-linolenic acid structured lipid microcapsules (ALA-SLM) is good; the solubility is 88.24±0.54g / 100g, indicating that walnut oil-α-linolenic acid structured lipid microcapsules (ALA-SLM) have good solubility; its loose density and tap density are 0.29±0.00g / cm3 and 0.33±0.01g / cm3 respectively, which are close to each other, indicating that the product density is low. The repose angle is 35.1±1.53°, indicating that ALA-SLM has good scattering properties.

[0136] Table 7 ALA-SLM physical and chemical indicators

[0137] Physical and chemical indicators result unit Moisture content 1.58±0.44 % Solubility 88.24±0.54 g / 100g Embedding rate 98.00±0.46 % Loose density 0.29±0.00 <![CDATA[g / cm 3 ]]> Tap density 0.33±0.01 <![CDATA[g / cm 3 ]]> Angle of repose 35.1±1.53 °

[0138] (II) Microscopic characterization of microcapsule products

[0139] Scanning electron microscope (SEM) observation: The microcapsule samples were subjected to gold spraying treatment and their morphology was observed by SEM, with the acceleration voltage set to 5 kV and the magnifications set to 5000× and 13000×.

[0140] SEM images of walnut oil-α-linolenic acid structured lipid microcapsules (ALA-SLM) are shown in Figure 2. Fig.10 As shown in the figure, the walnut oil-α-linolenic acid structured lipid microcapsules (ALA-SLM) prepared with soy protein isolate and β-cyclodextrin as wall materials are approximately spherical in shape, with clear outlines and smooth and compact surfaces. However, there are some surface depressions or cracks, which may be the result of differences in the emulsion during the freeze-drying process.

[0141] Laser confocal microscopy (CLSM) observation: 7.5 g of optimal walnut oil-α-linolenic acid structured lipid microcapsules (ALA-SLM) were redissolved in 100 mL of 60°C deionized water to obtain reconstituted emulsion. After diluting it 100 times, 1 mL was taken and rhodamine B, Nile red and FITC dyes were added to stain the protein, oil and carbohydrate respectively, and then the microscopic morphology was observed using a laser confocal microscope.

[0142] Laser confocal image of walnut oil-α-linolenic acid structured lipid microcapsules (ALA-SLM) Fig.11As shown (one point is selected for magnified analysis), by adjusting different fluorescence excitation wavelengths, the corresponding dyes show different colors at the corresponding wavelengths. By integrating the image, it can be found that the core material of walnut oil-α-linolenic acid structural lipid microcapsule (ALA-SLM) walnut oil-α-linolenic acid structural lipid (ALA-SL) is well embedded in the two wall materials of the microcapsule, and the soy protein isolate and β-cyclodextrin form a good microcapsule shell structure with a clearer outline.

[0143] (III) Particle size distribution and span value

[0144] The particle size of walnut oil-α-linolenic acid structured lipid microcapsule (ALA-SLM) emulsion was analyzed using a laser particle size analyzer to measure the particle size distribution of the emulsion.

[0145]

[0146] Among them, D10, D50, and D90 are the emulsion droplet diameters corresponding to 10%, 50%, and 90% of the cumulative distribution, respectively.

[0147] Particle size distribution, cumulative distribution and particle size related parameters of walnut oil-α-linolenic acid structured lipid microcapsules (ALA-SLM) are as follows Fig.12 As shown, it can be found that the particle size of ALA-SLM is generally normally distributed, with the particle size in the range of 1-10μm accounting for 89.15%, in the range of 0.1-1μm accounting for 5.79%, in the range of 10-44μm accounting for 5.06%, and the average particle size is 4.47±0.83μm. In addition, the Span value of the microcapsule is 1.92, indicating that the microcapsule particles are relatively uniform.

[0148] (IV) Fourier transform infrared spectroscopy

[0149] Weigh 0.30g of dried potassium bromide (110℃, 5h) and move it into the notch of the tablet press model. Press continuously for 5min at 27MPa to obtain potassium bromide tablets. Use a capillary to evenly apply the liquid sample to the potassium bromide tablets, and use a blank potassium bromide tablet as the background. Collect the spectrum in the scanning range of 400-4000cm-1 with a spectral resolution of 4cm-1, and scan 32 times to obtain the sample spectrum.

[0150] Fig.13 The infrared spectra of walnut oil-α-linolenic acid structured lipid microcapsules (ALA-SLM) (microcapsules) and their core materials and wall materials are compared. In the wave number range of 3000 to 3500 cm-1, it can be observed that the peaks of the microcapsules and the two wall materials are relatively broad, which clearly indicates the stretching vibration characteristics of the -OH bond (hydroxyl group). It is worth noting that since the hydroxyl content in these two wall materials is higher than that in the microcapsules, their peak intensities in this range are also more significant.

[0151] Further observation of the infrared spectrum of walnut oil-α-linolenic acid structured lipid (ALA-SL) (as core material) shows that the stretching vibration peak of C=C bond (carbon-carbon double bond) can be identified in the wave number range of 2800 to 3100 cm-1, which is mainly attributed to the fact that ALA-SL is rich in unsaturated fatty acids (such as oleic acid, linoleic acid and α-linolenic acid). However, on walnut oil-α-linolenic acid structured lipid microcapsules (ALA-SLM) (i.e. ALA-SL after microencapsulation), this vibration peak becomes less obvious, because the close combination of the wall material and the core material limits the free vibration of the unsaturated bonds in the core material. This change not only confirms the successful formation of ALA-SLM, but also reveals the important role of the wall material in protecting the chemical properties of the core material.

[0152] In summary, the spectra clearly show the differences in vibration characteristics of microcapsules, core materials and wall materials within a specific wavenumber range, especially the effect of hydroxyl content on peak intensity, and the regulatory effect of wall materials on the stretching vibration peak of C=C bond in the core material.

[0153] (V) Thermal stability determination

[0154] The mass loss rate curve of walnut oil-α-linolenic acid structured lipid microcapsules (ALA-SLM) was measured by thermogravimetric analyzer, and the results were expressed as mass loss rate.

[0155] Thermogravimetric analysis curve of walnut oil-α-linolenic acid structured lipid microcapsules (ALA-SLM) samples is shown in Fig.14 As shown in the figure, when the temperature gradually climbed to about 80℃, the TG curve of walnut oil-α-linolenic acid structured lipid microcapsules (ALA-SLM) showed a significant downward trend. As the temperature further increased to 182℃, a mass loss of about 4% was observed. Based on the initial mass of the microcapsules and the temperature range covered by the weight loss process, it can be reasonably inferred that the mass reduction at this stage is mainly due to the thermal evaporation of the water contained in the product. At around 309℃, the mass loss is large and the microcapsules lose weight further. When the temperature range is 183-414℃, the weight loss rate of ALA-SLM is about 80%, and the maximum weight loss rate appears near point c (309℃), which is mainly attributed to the loss of ALA-SL and the decomposition in the composite wall material; when the temperature is higher than 414℃, the weight loss curve tends to be flat, and ALA-SLM basically loses weight completely, indicating that it is completely carbonized. It can be seen that ALA-SLM exhibits good thermal stability below 182℃.

[0156] (VI) Storage stability determination

[0157] A certain amount of walnut oil-α-linolenic acid structured lipid (ALA-SL) and walnut oil-α-linolenic acid structured lipid microcapsules (ALA-SLM) were weighed and placed in sample bottles, respectively, and accelerated oxidation experiments were carried out in a 60℃ (333.15K) oven. Samples were taken every 5 days to determine the peroxide value. Taking the peroxide value as the evaluation index, walnut oil-α-linolenic acid structured lipid microcapsules (ALA-SLM) and walnut oil-α-linolenic acid structured lipid (ALA-SL) were respectively encapsulated in sample bottles, placed at 4℃, 25℃, and 40℃, and samples were taken every 5 days to determine the change of peroxide value over time under different temperature conditions.

[0158] Depend on Fig.15 It can be seen that the peroxide value of walnut oil-α-linolenic acid structured lipid (ALA-SL) and walnut oil-α-linolenic acid structured lipid microcapsules (ALA-SLM) showed an increasing trend with the extension of storage time. The slow growth in the initial stage reflects the mild progress of the oxidation reaction; while the accelerated growth rate in the later stage is attributed to the acceleration of the free radical chain reaction caused by the accumulation of peroxides. This phenomenon is a general law of oxidative degradation of oil compounds under the action of air, light, heat and other factors. After storage at 60℃ for 60 days, the peroxide value of ALA-SLM increased from 0.27g / 100g to 10.60g / 100g, while the change trend of the sample stored at 4℃ was relatively slow, and the peroxide value of the sample after storage for 60 days was only 1.91g / 100g. This may be due to the accelerated process of oxidation reaction in high temperature environment. After storage at 4°C, 25°C, 40°C and 60°C for 60 days, the peroxide value of ALA-SLM was reduced by 1.02, 1.06, 1.01 and 1.11 times compared with ALA-SL, indicating that the microcapsules of the present invention can delay the oxidation time of walnut oil-α-linolenic acid structural lipids (ALA-SL) and increase its storage time.

[0159] 7. In vitro simulated digestion assay

[0160] This study mainly measured and analyzed the digestion of simulated gastric fluid (SGF) and simulated intestinal fluid (SIF).

[0161] For simulated gastric fluid (SGF): First, completely dissolve 2g of NaCl in 900mL of distilled water. Subsequently, carefully adjust the pH of the solution to 1.2 using HCl to simulate the acidic environment in the stomach. After that, add 3.2g of pepsin to the solution to promote the initial digestion of food or medicine. Finally, the volume of the solution is fixed to 1000mL to ensure the accuracy of the concentration. The prepared SGF should be stored at 4°C to maintain the activity of pepsin and prevent it from being inactivated by high temperature.

[0162] For simulated intestinal fluid (SIF): First, 6.8 g KH2PO4 was dissolved in 800 mL distilled water to form a base solution. Then, 0.1 mol / L NaOH solution was used to gradually adjust the pH value of the base solution to 6.8 to simulate the neutral to weakly alkaline environment in the small intestine. At the same time, 10 g trypsin was dissolved in an appropriate amount of distilled water to ensure that it was completely dissolved. Then, the trypsin solution was mixed evenly with the previously prepared KH2PO4 solution, and the total volume was fixed to 1000 mL. Similarly, SIF should also be stored at 4 ° C to maintain the activity of trypsin and prevent it from being inactivated due to temperature changes. The sustained release data of microcapsules can usually be fitted with the following model to the core material release rate curve in gastrointestinal fluid to infer the release mechanism. The core material release rate and various models are shown in Table 7. Among them, m is the mass of oil released by microcapsule digestion; M is the total oil content of the microcapsule; Q is the release rate; t is time (min); a is the slope of the equation; b is the intercept of the equation.

[0163]

[0164] Table 7 Mathematical fitting model

[0165]

[0166] In such Fig.16 During the release of the core material of the walnut oil-α-linolenic acid structured lipid microcapsules (ALA-SLM) microcapsules shown in the figure, ALA-SLM exhibited significant sustained-release characteristics under an in vitro simulated digestion environment. Specifically, in the simulated gastric fluid (SGF) stage, although the core material began to release, its rate was relatively slow, reaching only 33.43% of the release rate, indicating that the microcapsules can effectively protect the core material from being released prematurely at this stage. As the digestion process entered the simulated small intestinal fluid (SIF) stage, the release rate of the core material accelerated significantly. After 5 hours of simulated digestion, the core material release rate climbed to a high of 69.72%. This trend clearly reveals that the ALA-SLM microcapsule design of the present invention is intended to promote the gradual release of the core material in the intestine, thereby optimizing its bioavailability.

[0167] The release behavior of walnut oil-α-linolenic acid structured lipid microcapsules (ALA-SLM) in simulated gastric fluid (SGF) and simulated small intestinal fluid (SIF) was further analyzed. The fitting results in Table 8 showed that the process was highly consistent with the first-order kinetic equation, verifying the feasibility of analyzing its release mechanism through the first-order kinetic model.

[0168] Table 8 Fitting equations of microcapsules under SGF and SIF conditions

[0169]

[0170] Through single-factor experimental design and orthogonal optimization strategy, the optimal process parameters for preparing walnut oil-α-linolenic acid structured lipid microcapsules (ALA-SLM) by freeze-drying were successfully determined: the core-wall mass ratio was set to 1:4, a specific ratio of composite wall materials (soy protein isolate and β-cyclodextrin, the ratio was 1:3) was used, and its addition amount was optimized to 12g / 100mL; at the same time, the addition amount of the emulsifier combination (sucrose ester and monoglyceride, 1:1) was optimized to 0.6g / 100mL. Under this optimal condition, the prepared ALA-SLM sample showed excellent encapsulation efficiency, reaching 98.00%±0.46%. Thermogravimetric analysis revealed the good thermal stability of ALA-SLM, and significant mass changes only occurred when the temperature exceeded 182℃, showing its superior heat resistance. FTIR analysis strongly proved that ALA-SL was effectively and tightly wrapped by soy protein isolate and β-cyclodextrin, ensuring the stability of the core material. Further storage stability tests showed that after 60 days of storage at different temperatures (4°C, 25°C, 40°C, and 60°C), the peroxide value of walnut oil-α-linolenic acid structured lipid microcapsules (ALA-SLM) was significantly reduced compared to unencapsulated walnut oil-α-linolenic acid structured lipids (ALA-SL), which were reduced by 1.02 times, 1.06 times, 1.01 times, and 1.11 times, respectively, highlighting its excellent antioxidant protection ability. In vitro simulated digestion experiments revealed the unique sustained-release characteristics of ALA-SLM, that is, most of the core material is gradually released in the intestinal stage. This design of the microcapsules of the present invention not only improves bioavailability, but also helps to control the release rate of nutrients to meet specific health needs.

Claims

1. A walnut oil-α-linolenic acid type structured lipid microcapsule, characterized in that: The invention comprises a wall material, a core material and a compound emulsifier, wherein the wall material is a compound wall material solution, the compound wall material solution comprises soy protein isolate, β-cyclodextrin and distilled water, and the addition ratio of the soy protein isolate and β-cyclodextrin is 1:3; the core material is walnut oil-α-linolenic acid structural lipid; the compound emulsifier comprises monoglyceride and sucrose ester, and the wall material, the core material and the compound emulsifier are stirred evenly under the action of a shear emulsifier to form an oil-in-water emulsion and freeze-dried to form microcapsules.

2. The walnut oil-α-linolenic acid type structured lipid microcapsule according to claim 1, characterized in that: The addition ratio of the core material, the wall material and the compound emulsifier is 1:4:0.4-0.5; the walnut oil-α-linolenic acid structural fat is a structural fat rich in α-linolenic acid at the sn-2 position.

3. A method for preparing walnut oil-α-linolenic acid type structured lipid microcapsules, characterized in that: The following steps are involved: Step 1: Preparation of structural lipids rich in α-linolenic acid at the sn-2 position; S1. Enzymatic acid hydrolysis S11. Mix the α-linolenic acid product and walnut oil in a ratio of 1:1-5:1 (mol / mol) and deionized water in a ratio of 1%, and place in a screw-stoppered test tube; S12. 1-20% (w / w) lipase Novozym 435 was added to the test tube; S13. The reactants are thoroughly mixed, the test tube is filled with nitrogen to exclude oxygen, and then the test tube is tightly sealed; S14. Place the test tube on a shaker, set the speed to 200 r / min, and react at a temperature of 35-75°C for 8-48 hours to obtain an acid hydrolysis product; S2. Molecular distillation purification S21. placing the product of the enzymatic acid hydrolysis in a molecular distillation apparatus, setting the parameter conditions of the molecular distillation apparatus; performing molecular distillation on the enzymatic acid hydrolysis product to purify the crude product of the acid hydrolysis product; Step 2: Weigh 10-18g / 100mL of the composite wall material, dissolve it in 100mL of distilled water, and stir it at a constant temperature of 60°C for 30min using a magnetic water bath stirring pot to dissolve evenly; the composite wall material is prepared by using soy protein isolate and β-cyclodextrin in a ratio of 1:3 (w / w); Step 3: Add 2.0-6.0 g of the structured lipid product obtained in step 1, add 0.2-0.6 g / 100 mL of a compound emulsifier, and stir evenly under the action of a high-speed shear emulsifier to form a primary emulsion (15000 r / min 5 min); the compound emulsifier is prepared by using a monoglyceride: sucrose ester ratio of 1:1 (w / w); Step 4: homogenize, freeze-dry and store the obtained microcapsule product in a sealed container away from light.

4. The preparation method according to claim 3, characterized in that: The parameter conditions of the molecular distillation apparatus in step 1 are: preheating 80°C, feed 2mL / min, wall temperature 180°C, scraper 100r / min, condensed water 25°C, and pressure 1Pa.

5. The preparation method according to claim 3, characterized in that: In step 1, the molar ratio of α-linolenic acid to walnut oil is 3:1, the amount of lipase is 10%, the reaction temperature is 55° C., and the reaction time is 24 hours.

6. The method according to claim 3, characterized in that: In step 1, the molar ratio of α-linolenic acid to walnut oil is 2.65:1, the amount of lipase is 7.65%, the reaction temperature is 55° C., and the reaction time is 38 h.

7. The method according to claim 3, characterized in that: The α-linolenic acid content in the α-linolenic acid product in step 1 is ≥ 70%.

8. The method according to claim 3, characterized in that: The amount of wall material added is 10g / 100mL, that is, 2.5g / 100mL of structural fat is added, and the amount of emulsifier added is 0.6g / 100mL.

Citation Information

Patent Citations

  • Powdered oil for replacing oil packet of instant noodles and preparation method thereof

    CN102783628A

  • Method for preparing proportioned structured lipid by using lipase to catalyze mulberry seed oil and alpha-linolenic acid

    CN109007239A

  • Preparation method and application of grease with customized sn-2 fatty acids

    CN111893143A